2013
DOI: 10.1155/2013/769489
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Patterns in the Interfollicular Caucasian Scalps: Influences of Age, Gender, and Alopecia

Abstract: Skin ageing and gender influences on the scalp have been seldom studied. We revisited the changes in the interfollicular scalp. The study was performed on a population of 650 volunteers (300 women and 350 men) for over 7 years. Three age groups were selected in both genders, namely, subjects aged 20–35, 50–60, and 60–70 years. The hair status was further considered according to nonalopecic and alopecic patterns and severity (discrete, moderate, and severe). Biopsies from the parietal area were processed for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…With age, as described by previous works (carried out on Caucasian subjects), the human scalp undergoes epidermal and dermal changes, leading to progressive thickening of SC and epidermis together with a denser and reticulated dermis, all concurring to establish a more rigid scalp skin structure . These changes were shown amplified during the development of alopecia . Altogether, our own data on scalp appear in agreement with these quoted works and seem paving the road toward future evaluations of scalp‐care dedicated products.…”
Section: Discussionsupporting
confidence: 91%
“…With age, as described by previous works (carried out on Caucasian subjects), the human scalp undergoes epidermal and dermal changes, leading to progressive thickening of SC and epidermis together with a denser and reticulated dermis, all concurring to establish a more rigid scalp skin structure . These changes were shown amplified during the development of alopecia . Altogether, our own data on scalp appear in agreement with these quoted works and seem paving the road toward future evaluations of scalp‐care dedicated products.…”
Section: Discussionsupporting
confidence: 91%
“…The interstitial extracellular matrix present between collagen bundles contains a mixture of hyaluronic acid, versican, and other glycosaminoglycans [ 39 ]. Dermal water is bound to these hydrophilic compounds.…”
Section: Hrt and The Dermal Extracellular Matrixmentioning
confidence: 99%
“…The number of Ki67‐positive epidermal cells was counted and there was no significant difference in the number when comparing male to female subjects. There was a significant reduction in Ki67‐positive epidermal keratinocytes of 22% in old males compared to young males and a 19% reduction in old females compared to young females . The subjects in our dandruff study were age‐matched so the differences in Ki67 expression we observed cannot be attributed to age.…”
Section: Discussionmentioning
confidence: 68%
“…It is a well‐established histological marker of proliferating cells often used in the analysis of skin epithelial tumours . The expression of Ki67 has been evaluated in human scalp skin previously, but only in relation to skin ageing .…”
Section: Introductionmentioning
confidence: 99%